10x+25x-7=7(5x+6)

Simple and best practice solution for 10x+25x-7=7(5x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x+25x-7=7(5x+6) equation:



10x+25x-7=7(5x+6)
We move all terms to the left:
10x+25x-7-(7(5x+6))=0
We add all the numbers together, and all the variables
35x-(7(5x+6))-7=0
We calculate terms in parentheses: -(7(5x+6)), so:
7(5x+6)
We multiply parentheses
35x+42
Back to the equation:
-(35x+42)
We get rid of parentheses
35x-35x-42-7=0
We add all the numbers together, and all the variables
-49!=0
There is no solution for this equation

See similar equations:

| X+6y=37 | | 28=6v+2v | | -13-2a=-8a+79(54+5a) | | 5+2(-4c+20)=17-c | | 3y+10=2(-5y+5)-2y | | 1/2(h)-12=-5 | | 3x-41=-2(-2x-7)-6x | | -7y+7(1+2y)=-2y-11 | | (1/2)h-12=-5 | | -8-3(44-5y)=-2y+13 | | 6p+4/6=4p-83 | | 20×x=50 | | -2k-25=2(-4k-39)-1 | | -2x-15=10-2x-25 | | 4^2+20x=0 | | 8n=–6+7n | | 5+7x=-128 | | 7(-3y-5)+9=-8y | | 9x=5x+4(2x-13) | | -10a-24(5a+48)=-2a | | -5+24=-8t-15 | | 11=10(3a+31)+1 | | 3^(2x-3)=4^x | | 12=4(4y-18)-9y | | -43(3z-35)-5=-4z | | (3x-1)(2x-9)=90 | | 8(1)+2y=-6 | | 2(2x-6)-8=4(3x-2) | | 9x-18=5x-2 | | 2b-3b=+4b | | s=0.8(24) | | 6912=(18x+6x)*18x |

Equations solver categories